Diversity, composition, taxa biomarkers, and functional genes of fish gut microbes in peat swamp forests and its converted areas in North Selangor, Malaysia - Saadu, Hamidu; Sutra, Jumria; Ismail, Ahmad; Zulkifli, Syaizwan Zahmir; Amal, Mohammad Noor Azmai (Universiti Putra Malaysia Press, 2021)
The aquatic organisms in peat swamp forests are under threat due to habitat degradation resulting from human activities. This study determines the fish gut microbes’ diversity, composition, taxa biomarkers, and functional genes in peat swamp forests and its converted areas in North Selangor, Malaysia. Three undisturbed and disturbed areas nearby the peat swamp forests were selected. First, the 16S amplicon metagenomic analysis was conducted to assess the composition and diversity of bacterial communities in fish gut contents from both areas. Then, Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) and Linear discriminant analysis Effect Size (LEfSe) were used to predict disease/pathogen related functional genes. This study revealed Proteobacteria, Firmicutes, Bacteroidetes, Fusobacteria, and Actinobacteria as the predominant phyla in both studied areas. In contrast, bacterial community profiles of disturbed and undisturbed areas were slightly dissimilar. Metagenome predictions revealed that genes are related to metabolism, environmental information processing, genetic information processing, cellular processes, human diseases, and organismal systems. Further investigation revealed six potential biomarker genes, including chronic myeloid leukaemia in an undisturbed area, Vibrio cholerae infection, bladder cancer, pathogenic Escherichia coli infection, Staphylococcus aureus infection, and pertussis in disturbed areas. This study revealed that the fish gut microbiome could be used as an indicator in comparing the undisturbed and disturbed ecosystems.